KANDUNGAN KIMIA DAN SIFAT SERAT ALANG-ALANG (Imperata cylindrica) SEBAGAI GAMBARAN BAHAN BAKU PULP DAN KERTAS - Budi Sutiya (Universitas Lambung Mangkurat, 2012)
Imperata grassland can be found in South Kalimantan in great amount and is known as a nuisance weed plants. The research is conducted to find out reed’s chemical content and its properties to know the description of the nature of the fiber as raw material for pulp and paper. The result of the research shows the water content of Imperata grassland is 97.76%, extractive content is 8.09%, the lignin content is 31.29%; 59.62% of holocellulose, 40.22% of alphacellulose, and 18.40% of pentosan. The second phase of the study of Imperata grassland fiber anatomy have been completed with the results of the fiber diameter is equal to 20 μm; 8.75 μm of lumen diameter, cell wall thickness is 5.65 μm and fiber length is 2.19 mm mm. Value of the derivative dimension of the Imperata grassland fiber obtained as follows: runkel ratio is 1.29; 42.24 (%) of mulstep number, power loom is 109.37, the valueof flexibility is 0.44 and stiffness coefficient is 0.28